Barrier materials for prevention of surgical adhesions: systematic review. Issue 3 (6th June 2022) - Waldron, Michael Gerard; Judge, Conor; Farina, Laura; O'Shaughnessy, Aoife; O'Halloran, Martin
Abstract: Background: Postoperative surgical adhesions constitute a major health burden internationally. A wide range of materials have been evaluated, but despite constructive efforts and the obvious necessity, there remains no specific barrier widely utilized to prevent postoperative adhesion formation. The aim of this study was to highlight and characterize materials used for prevention of postoperative surgical adhesions in both animal and human studies. Methods: A systematic review was performed of all original research articles presenting data related to the prevention of postoperative adhesions using a barrier agent. All available observational studies and randomized trials using animal models or human participants were included, with no restrictions related to type of surgery. PubMed and Embase databases were searched using key terms from inception to August 2019. Standardized data collection forms were used to extract details for each study and assess desirable characteristics of each barrier and success in animal and/or human studies. Results: A total of 185 articles were identified for inclusion in the review, with a total of 67 unique adhesion barrier agents (37 natural and 30 synthetic materials). Desirable barrier characteristics of an ideal barrier were identified on review of the literature. Ten barriers achieved the primary outcome of reducing the incidence of postoperative adhesions in animal studies followed with positive outputs in human participants. A further 48 materials had successful results from animal studies, but with no human study performed to date. Discussion: Multiple barriers showed promise in animal studies, with several progressing to success, and fulfilment of desirable qualities, in human trials. No barrier is currently utilized commonly worldwide, but potential barriers have been identified to reduce the burden of postoperative adhesions and associated sequelae. Abstract : In this systematic review, we evaluated barrier materials utilized for the prevention of postoperative adhesions. We assessed 67 adhesions barriers from 185 animal and human studies in the published literature, with each barrier material was assessed based on achieving the primary goal of postoperative adhesion reduction and on the potential ability to achieve a standardized set of desirable characteristics. Multiple barriers showed promise in animal studies, with several progressing to success in and fulfilment of desirable qualities in human trials.